Factors influencing same-day discharge after minimally invasive hysterectomy for malignant and non-malignant gynecological diseases: a systematic review and meta-analysis - Liu, Jia; Chen, Yali; Tan, Xin; Chen, Hengxi (Frontiers in Oncology, 2024)
Objective To explore the factors influencing the successful implementation of same-day discharge in patients undergoing minimally invasive hysterectomy for malignant and non-malignant gynecological diseases. Method We searched PubMed, Embase, Cochrane Central Register of Controlled Trials, International Clinical Trials Registry Platform, and Clinical Trials.gov from inception to May 23, 2023. We included case-control and cohort studies published in English reporting same-day discharge factors in patients undergoing minimally invasive hysterectomy for malignant and non-malignant gynecological diseases. STATA 16.0 was used for the meta-analysis. Risk factors were assessed using odds ratios (OR) (relative risk (RR)/hazard ratios (HR)) with 95% confidence intervals (CI), and logistic regression determined the same-day discharge rate (%). Results We analyzed 29 studies with 218192 patients scheduled for or meeting same-day discharge criteria. The pooled rates were 50% (95% CI 0.46-0.55), and were similar for malignant and non-malignant gynecological diseases (48% and 47%, respectively). In terms of basic characteristics, an increase in age (OR: 1.03; 95% CI: 1.01–1.05), BMI (OR: 1.02; 95% CI: 1.01–1.03), and comorbidities including diabetes and lung disease were risk factors affecting SDD, while previous abdominal surgery history (OR: 1.54; 95% CI: 0.93–2.55) and hypertension (OR: 1.53; 95% CI: 0.80–2.93) appeared not to affect SDD. In terms of surgical characteristics, radical hysterectomy (OR: 3.46; 95% CI: 1.90–6.29), surgery starting after 14:00 (OR: 4.07; 95% CI: 1.36–12.17), longer surgical time (OR: 1.03; 95% CI: 1.01–1.06), intraoperative complications (OR: 4.68; 95% CI: 1.78–12.27), postoperative complications (OR: 3.97; 95% CI: 1.68–9.39), and surgeon preference (OR: 4.47; 95% CI: 2.08–9.60) were identified as risk factors. However, robotic surgery (OR: 0.44; 95% CI: 0.14–1.42) and intraoperative blood loss (OR: 1.16; 95% CI: 0.98–1.38) did not affect same-day discharge. Conclusions An increase in age, body mass index, and distance to home; certain comorbidities (e.g., diabetes, lung disease), radical hysterectomy, surgery starting after 14:00, longer surgical time, operative complications, and surgeon preference were risk factors preventing same-day discharge. Same-day discharge rates were similar between malignant and non-malignant gynecological diseases. The surgery start time and body mass index have a greater impact on same-day discharge for malignant diseases than non-malignant diseases.